TREATMENT PLAN PROPOSALS TO THE PATIENT WITH PARTIAL EDENTATION - Roxana Ionela Vasluianu; Catalina Holban Cioloca; Magda Antohe; Bogdan Bulancea; Norina Consuela Forna (Romanian Dental Association for Education, 2019)
The loss of the remaining natural teeth is a major and irreversible procedure for the patient. The prognosis for each remaining tooth should be assessed carrefully. A treatment plan is a proposal and can change due to a lot of reasons, including the patient's ambivalence, prevailing clinical presentations, unforeseen complications and ﬁnancial burdens. The presence of gross carries or advanced periodontal disease,cupled with a reluctance of the patient to respond to oral hygiene instruction, makes the decision of whether or not to extract the teeth a simple one. The loss of teeth may lead patients to seek care for functional reasons if they notice diminished function to a level that is unacceptable to them. Many prosthodontic treatments involves pretreatment and proprosthetic treatments, crown lengthening and intervention surgery on the level of the ridge.